POPULATION BIOLOGY OF Panopeus lacustris DESBONNE 1867 ( BRACHYURA: PANOPEIDAE ) IN PIAUÍ COASTAL, BRAZIL - dos Santos Filho, Luiz Gonzaga Alves; dos Santos, Sidely Gil Alves Vieira; de Góes, João Marcos; Fernandes-Góes, Lissandra Corrêa (Arquivos de Ciências do Mar, 2018)
Specimens of Panopeus lacustris were identified, sexed, and measured to obtain the following dimensions: carapace width, carapace length, body height, the propodus major length, the propodus major wide, the propodus major height, abdomen width and gonopodium length. The average carapace width (CW) and the average weight differed significantly between the sexes. The proportion of righthanded crabs was significantly higher than the left-handed. Males were more frequent in classes 22.41|–25.75 mm, and females in class 19.06|–22.41 mm. Biometric data were subjected to regression using a power function. The morphological sexual maturity width of the carapace showed an average of 12.32 mm on males and 12.00 mm on females. However, it was observed that 50% of physiologically mature crabs presented 11.35 mm of CW for males and 10.61 mm for females. The sex ratio of all crabs analyzed was 1:1.15 (males:females). The data collected during this study suggest that the reproductive period of this species is continuous. The results of this study are common to populations of Brachyura, and indicate that the population of P. lacustris is stable in the environment.